Annual Development Performance of Fixed Honeybee Colonies Linked with Chemical and Mineral Profile of Bee Collected Pollen. Issue 8 (15th July 2022) - Topal, Erkan; Çakıcı, Neslihan; Mărgăoan, Rodica; Takma, Çiğdem; Güney, Fazıl; Kösoğlu, Mustafa; Cornea‐Cipcigan, Mihaiela; Atmaca, Hilal
Abstract: Climate change affects plant phenology and, as a result, can damage nectar and pollen sources, which are the basic needs of bees during flowering. This situation creates nutritional stress for bee colonies in the region. Changing climatic conditions, the use of agricultural lands adversely affects honeybees and beekeepers. The aim of this study is to determine the annual development performance of fixed honeybee colonies linked with the chemical and mineral profile of bee collected pollen. According to the research findings, in terms of colony development parameters, the number of bee frames (9.17) was found to be at the highest level in May, and in terms of brood area (4652.35 cm 2 ) in April ( P< 0.05). March, April, and May are the most abundant months in terms of pollen collection of the colonies ( P< 0.05). The pollen samples collected are rich in potassium, sodium, calcium, magnesium, silicon, and iron. There are differences between months in terms of pollen sources and mineral levels. Especially in stationary beekeeping, additional feeding is required during critical periods. The existing flora is insufficient for the future of the honey bee. In periods when the flora is weak, important plants for the honey bee should be grown in the region. Abstract :